Optimizing the Genetic Transformation of Coffea arabica Using Agrobacterium tumefaciens - Diana Molina; Ricardo Acuña (International Journal of Plant Biology)
The genetic transformation of Coffea arabica L. is an alternative strategy for obtaining plants with agronomic traits of interest that is less time-consuming than conventional breeding methods. Given the importance of coffee cultivation in Colombia, this study evaluated the main factors interfering with the genetic transformation of C. arabica using Agrobacterium tumefaciens. An efficient and reproducible method was accordingly developed that involved propagating “early” embryogenic calli in a liquid proliferation medium supplemented with 3 mg L−1 BAP for eight months, followed by sonication for 300 s in a suspension of LBA4404 OD600 of 0.5, harboring pCambia1301, and then incubation in this same suspension for 1 h. The vector pCambia1301 contained the uidA gene under control of the 35S promoter. A micropipette was used to remove the Agrobacterium suspension from the embryogenic callus. The remaining Agrobacterium suspension was blotted off by placing the embryogenic callus on filter paper. The embryogenic callus was then co-cultured for four days in a solid differentiation medium supplemented with 100 µM acetosyringone on filter paper. Subsequently, the embryogenic callus was post-cultured for four days in liquid differentiation medium under constant shaking at 100 rpm with 300 mg L−1 Cefotaxime, followed by selection with 50 mg L−1 hygromycin at 26 °C in the dark, with subcultures at 20-day intervals until somatic embryos were formed for subsequent culturing in germination medium. Molecular analysis confirmed the presence of the uidA gene in coffee seedlings transformed with strains LBA4404 and EHA105 and vectors pCambia1301 and pCambia2301 by polymerase chain reaction (PCR) analysis. This method successfully enables the stable integration of genes of interest in the coffee plant genome.